Design and Development of a Learning Design Virtual Internship Program - Ruggiero, Dana; Boehm, Jeff (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
Incorporation of practical experience in learning design and technology education has long been accepted as an important step in the developmental process of future learning designers. The proliferation of adult online education has increased the number of graduate students who are in need of a practical internship placement but have limited options due to work and family obligations. An international virtual internship program provides opportunity for non-traditional students to participate in a practical experience regardless of their physical location and other obstacles.